Courts and Qurʾāns: "ʿUthmānī" Codices from the Caliph's Residence in Medina to Topkapı Palace in Istanbul. - Talmon-Heller, Daniella (Al-Masaq: Journal of the Medieval Mediterranean, 2026)
This paper analyses the place of so-called "ʿUthmānī" codices of the Qurʾān in the courtly culture of Islamic dynasties. It highlights how these manuscripts transcended their role as master-copies of sacred scriptures to become potent symbols of political power, legitimacy, and religious affiliation. The study examines these Qurʾāns as charismatic sacred relics and instruments of royal display, reinforcing the authority and prestige of the ʿAbbāsids, Umayyads of al-Andalus, Būrids, al-Muwaḥḥids, Marīnids, Mamlūks, Īl-Khānids and Ottomans. Tracing "biographies" of such codices, the narrative demonstrates their functions as ritual objects and items of personal piety within courts and adjacent great-mosques and shrines; devices of statecraft and diplomacy; and emblems of local identity, sometimes resistance, for the wider community of believers. The research draws on medieval Arabic sources, manuscript catalogues, contemporary historical and codicological research, and Annette Weiner's theoretical framework, defining inalienable possessions – objects that resist commodification due to their deep symbolic significance.